Negotiating Legitimacy, Enacting Care: A Phenomenological Study of Women’s Leadership in Start-ups in Makassar, Indonesia - Dipoatmodjo, Tenri Sayu Puspitaningsih (Maksimal Jurnal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
While start-ups are often celebrated as agile and egalitarian spaces that disrupt traditional hierarchies, women leaders within them continue to navigate gendered expectations, institutional ambiguities, and cultural constraints—particularly in emerging entrepreneurial ecosystems of the Global South. Drawing on in-depth phenomenological interviews with 10–12 women leading start-up teams across technology, creative, and service sectors in Makassar, Indonesia, this study explores how these leaders construct, enact, and sustain leadership amidst intersecting global norms and local socio-cultural logics. Findings reveal that participants engage in continuous relational labor to assert legitimacy, craft hybrid leadership models that blend strategic agency with communal care, and reinterpret domestic roles as both resources and constraints. Rather than conforming to dominant masculine entrepreneurial archetypes, they mobilize narrative, empathy, and ethical stewardship to build team cohesion and organizational identity. This research contributes to transnational feminist scholarship by centering the lived experience of women in Southeast Asian start-ups, challenging universalist assumptions in entrepreneurship theory, and highlighting the need for culturally grounded, gender-responsive support ecosystems.